HALAL CERTIFICATION ASSISTANCE FOR SMES: ENHANCING COMPETITIVENESS AND CONSUMER TRUST - Naufaila Salsabila (Cahaya Ilmu Bangsa, 2024)
Halal certification is crucial in the food and beverage industry to increase consumer trust. However, SMEs often face various challenges in obtaining this certification. This program aims to provide assistance to SMEs in the halal certification process to enhance their competitiveness and consumer trust. Using a participatory approach with data collection methods including interviews, surveys, and observations.Several SMEs successfully obtained halal certification after participating in the assistance program, with increased understanding and readiness to meet certification requirements. Halal certification assistance effectively helps SMEs improve their competitiveness and consumer trust. This program can be replicated and improved to support more SMEs in the future.